FABRICATION OF SILENCER - Yashwant .D. Chavan; Satish . R. Kadam Om Shahaji Thite, Ganesh Rajendra survase , Laxmikant Sanjay Kulkarni (International Journal of Innovations in Engineering Research and Technology, 2022)
The air pollution is the major problem on the earth. The major pollution on the earth is caused by automobiles. IC engines produces undesirable emission such as unburnt hydrocarbon (HC), carbon monoxides (CO), oxides of nitrogen (NOx), oxides of Sulphur (SOx), and solid carbon particle. So it is necessary that serious attempts should be made to conserve earth’s environment from degradation. An aqua silencer is an attempt in this direction. It mainly deals with control of emission and noise from the IC engine. An aqua silencer is placed at the exhaust pipe of an engine. Aqua Silencer is a modification of a conventional silencer which is aimed at the reduction of emission from the exhaust of an IC engine into the atmosphere and also to reduce the noise by damping methods which involves water. It uses the cheap chemicals like lime water, charcoal and water in the design and fabrication of the silencer to reduce the noise and toxic emission from IC engine. Sound produced in water is less audible than in atmosphere. This principle is used to reduce the noise level of the internal combustion engine Hence our attempt is to replace the conventional silencer by aqua silencer ti reduce the air and noise pollution.